Control system synthesis of formation of carbon products - Zhuchenko, Oleksii (Technology audit and production reserves, 2017)
The object of research is the process of formation of carbon products. The production of carbon products is characterized by considerable resource and energy intensity, therefore the actual task is to increase the efficiency of this production by introducing the optimum operating modes of its component technological processes. One of the main technological processes in the production of carbon products is the process of their formation by squeezing of the electrode mass through a mouthpiece of the corresponding shape in a hydraulic press. All inherited properties that determine the quality of finished products are laid at the stage of pressing the electrode blanks The analysis of the existing control systems for the process of formation of carbon products shows that the formation process is a typical cyclic process. For such processes, the control task is, as a rule, to implement such controls that would ensure that one or more output variables are tracked by a predetermined path of motion, which is repeated from cycle to cycle. A new control system is proposed that provides for iterative learning control in formation of the electrode mass by squeezing through a mouthpiece of the corresponding shape in a hydraulic press. The corresponding ILC algorithm is proposed. Thanks to this solution, a high quality control is provided in the absence of initial uncertainties and external disturbances.